Simultaneous pheochromocytoma and third‐degree atrioventricular block in 2 dogs. (19th September 2013) - Mak, Genevieve; Allen, Justin
Abstract Objective To describe the occurrence of pheochromocytoma with third‐degree atrioventricular (AV) block in 2 dogs. Case Series Summary Two dogs were referred for echocardiograms and further diagnostic and therapeutic treatment for third‐degree AV block. Abdominal ultrasound of 1 dog revealed an adrenal mass, while that of the other dog revealed bilateral adrenal masses. While undergoing treatment, 1 dog experienced cardiac arrest and could not be revived with cardiopulmonary resuscitation, and the other dog was humanely euthanized. Histological findings of the masses were consistent with pheochromocytomas. New or Unique Information Provided To the authors' knowledge, this is the first report with histologic evidence of pheochromocytoma and clinical presentation of third‐degree AV block in dogs. In human literature, simultaneous presentation of both disease states is rare and has been infrequently reported.